Hot Water Pretreatment of Lignocellulosic Biomass: An Effective and Environmentally Friendly Approach to Enhance Biofuel Production. Issue 10 (1st September 2016) - Yan, Lishi; Ma, Ruoshui; Li, Liangzhi; Fu, Jiaolong
Abstract: Hot water pretreatment without usage of chemicals is a particularly attractive approach for pretreatment of lignocellulosic biomass due to its fewer safety and environmental concerns as well as relatively low cost. However, a prohibitive amount of sugar degradation products limits the efficiency of such pretreatment, and excessive water consumption accompanied with the over‐diluted sugar streams still impedes the implementation of this pretreatment to be an economically viable pathway. These limitations are associated with the scant attention of water‐biomass interaction mechanism and engineering aspects regarding kinetic modeling and reactor configurations. This review aims at investigating those critical factors in terms of chemistry and engineering fundamentals in order to understand the correct axiomatic approaches needed to advance this technology. Various reactor configurations and kinetic models are evaluated to explore optimization strategies toward application. Abstract : Pretreatment of lignocellulosic biomass is essential for overcoming its inherent recalcitrance prior to enzymatic hydrolysis and fermentation of its carbohydrate components into biofuels and bioproducts. Pretreatment of lignocellulosic biomass with hot water without chemicals is a particularly promising approach due to less safety and environmental concerns as well as relatively low costs.